Mekanisme Pengangkatan Pegawai Syara’ Perspektif Fikih Imamah (Studi Kasus di Desa Lasori, Kabupaten Buton Tengah, Provinsi Sulawesi Tenggara): The Mechanism of Appointment of Syara’ Officers from the Perspective of Imamah Fiqh (A Case Study in Lasori Village, Central Buton Regency, Southeast Sulawesi Province) - Ahmad Syaripudin; Aldin Aldin (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2026)
This study aims to determine the review of imamah fiqh regarding the mechanism for appointing syara' officers in Lasori Village, Central Buton Regency, Southeast Sulawesi Province. The problems raised in this research are: First, what is the mechanism for appointing syara' mosque officers in Lasori? Second, what is the perspective of imamah fiqh on the mechanism for appointing syara' officers in Lasori? This research uses field research with qualitative data presentation. Data collection techniques include observation, interviews with relevant parties, and document analysis. The results show: First, the appointment mechanism involves several stages: (1) assessment of candidates by senior syara' officers; (2) sending a representative to inform the candidate; (3) interviewing the candidate; (4) appointment with a mandatory payment of IDR 180,000; (5) recitation of prayers for the new officer. Second, from the perspective of imamah fiqh, this mechanism is not fully in accordance with Islamic law because it does not consider the important criteria for an imam as explained in the Qur'an and hadith, such as knowledge of the Qur'an, understanding of the Sunnah, and precedence in Islam.